1993
DOI: 10.1038/364249a0
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase Cα activates RAF-1 by direct phosphorylation

Abstract: The kinase Raf-1 can be activated by treatment of cells with mitogens and by the protein kinase C (PKC) activator 12-O-tetradecanoyl-phorbol-13-acetate (TPA) (reviewed in refs 1,2). Activated Raf-1 triggers a protein kinase cascade by direct phosphorylation of MAP kinase kinase, resulting in phosphorylation of ternary complex factor and Jun by MAP kinase. Here we investigate the molecular mechanism and biological consequences of PKC alpha-mediated Raf-1 activation in NIH3T3 fibroblasts. PKC alpha directly phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
748
5
8

Year Published

1995
1995
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,239 publications
(799 citation statements)
references
References 12 publications
38
748
5
8
Order By: Relevance
“…One possible mechanism for integration of the PKC signal into the MAPK cascade, which is consistent with its activation by G protein-coupled receptors [76], is that PKC is required to activate Raf-1. In addition to tyrosine kinase-dependent phosphorylation of Raf-1 by polypeptide growth factors, direct phosphorylation by PKCa is reported to stimulate the catalytic activity of Raf-1 [96]. In support of this, direct activators of PKC (phorbol esters) [82], as well as agonists which utilize the PKC pathway such as ET-1 [76] and 5-HT [50], activate Raf-1 kinase activity in airway smooth muscle cells.…”
Section: Interaction Of Protein Kinase C With Other Signalling Molecumentioning
confidence: 92%
“…One possible mechanism for integration of the PKC signal into the MAPK cascade, which is consistent with its activation by G protein-coupled receptors [76], is that PKC is required to activate Raf-1. In addition to tyrosine kinase-dependent phosphorylation of Raf-1 by polypeptide growth factors, direct phosphorylation by PKCa is reported to stimulate the catalytic activity of Raf-1 [96]. In support of this, direct activators of PKC (phorbol esters) [82], as well as agonists which utilize the PKC pathway such as ET-1 [76] and 5-HT [50], activate Raf-1 kinase activity in airway smooth muscle cells.…”
Section: Interaction Of Protein Kinase C With Other Signalling Molecumentioning
confidence: 92%
“…Once again, Raf-1 was found associated with c-N-ras in both cell lines. The possibility that other Raf family kinases (B-Raf and ARaf) might associate with Ras in vivo was tested using the pan-reactive Raf monoclonal antibody, PBB-1 (Kolch et al, 1990). Figure 6g indicated that, in V12H10 and K61N10 cells, only one Raf family kinase co-immunoprecipitated with N-ras, and this Raf protein co-migrated with Raf-1.…”
Section: Raf-1 Co-immunoprecipitates With N-ras But Not Ha-rasmentioning
confidence: 99%
“…At the membrane Raf-1 is activated partially by interactions with Ras (Drugan et al, 1996;Mineo et al, 1997;Roy et al, 1997;Stokoe and McCormick, 1997) but also by other mechanisms that require phosphorylation of tyrosine (Fabian et al, 1993;Dent et al, 1995a;Marais et al, 1995;Jelinek et al, 1996) and the presence of certain serine and threonine residues which may be phosphorylated (Fabian et al, 1993;Dent et al, 1995a;Diaz et al, 1997). Candidate kinases that may regulate Raf-1 activity at the plasma membrane include the sca old protein KSR (Yao et al, 1995;Therrien et al, 1996;Zhang et al, 1997), protein kinase C (Kolch et al, 1993), cAMP-dependent protein kinase or protein kinase A (Kikuchi and Williams, 1996) and AMP-activated protein kinase (Sprenkle et al, 1997). Activated Raf-1 phosphorylates and activates MEK1 and MEK2 which in turn phosphorylate and activate ERK1 and ERK2 (Marais and Marshall, 1996;Pritchard and McMahon, 1997).…”
Section: Introductionmentioning
confidence: 99%